Preparation method of photovoltaic glass mildew-proof paper
By preparing a mildew-resistant coating of nano-silver coated with carboxyethyl chitin, modified montmorillonite and porous polylactic acid composite on the surface of photovoltaic glass anti-moldering paper, the problem of mold growth in photovoltaic glass anti-molding paper in humid environments is solved, and the long-term anti-mold effect is achieved and the product's performance is improved.
Patent Information
- Application Number
- CN202311101072.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2043-08-30
AI Technical Summary
Photovoltaic glass anti-mold paper can easily lead to mold growth in humid environments, affecting the protective performance of the product and limiting its scope of use.
Nanosil coated carboxyethyl chitin, modified montmorillonite and porous polylactic acid are used to prepare a composite material, and added to polyvinyl alcohol solution to prepare a mildew coating solution, and coated on the surface of photovoltaic glass anti-mold paper to form a mildew coating.
It significantly improves the anti-mold property and anti-mold time of photovoltaic glass anti-mold paper, enhances its performance under extreme conditions, and provides new ideas for other long-term anti-mold packaging materials.
Smart Images

Figure CN117026683B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of photovoltaic glass mildew-proof paper, and belongs to the field of papermaking.
[0002] Background technology Photovoltaic glass protective film is usually a protective film processed from PE film or PVC film. This film can prevent the surface of the glass from being scratched and dirty during production, transportation, and installation, and has a good anti-mildew effect in humid environments. Among them, the implementation of "Plastics: Carbon Footprint and Environmental Footprint of Bio-based Plastics Part 1: General Principles" will provide a standard technical basis for the evaluation of the carbon footprint and environmental footprint of bio-based plastics. It is expected that the demand for replacement of non-degradable plastic products will gradually release. Therefore, photovoltaic glass anti-mildew paper will replace the current photovoltaic glass protective film based on PE and PVC substrates.
[0003] Photovoltaic glass mildew-proof paper is made from plant fibers through a papermaking process. Its wide availability, mature processing technology, and superior product performance make it a viable alternative to PE and PVC. However, because it primarily consists of carbohydrates, it can easily lead to mold growth in humid environments, producing black mold spots. This affects the product's protective properties and limits its use. Therefore, to enhance its protective performance and preserve the appearance of photovoltaic glass panels, improvements to the performance of photovoltaic glass mildew-proof paper are necessary. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for preparing photovoltaic glass mildew-proof paper. The present invention can improve the mildew resistance of photovoltaic glass mildew-proof paper and has the advantages of good mildew resistance effect and long mildew resistance time.
[0005] The technical solution of the present invention is a method for preparing photovoltaic glass mildew-proof paper, comprising the following steps:
[0006] Step 1: preparing nano-silver coated carboxyethyl chitin by using silver nitrate and carboxyethyl chitin;
[0007] Step 2: preparing a nano-silver coated carboxyethyl chitin-modified montmorillonite composite material by using nano-silver coated carboxyethyl chitin and modified montmorillonite;
[0008] Step 3, using nano-silver coated carboxyethyl chitin and porous polylactic acid to prepare a nano-silver coated carboxyethyl chitin-porous polylactic acid composite material;
[0009] Step 4: adding the nano-silver coated carboxyethyl chitosan-modified montmorillonite composite material to the polyvinyl alcohol solution and stirring to obtain an anti-mildew coating liquid A; adding the nano-silver coated carboxyethyl chitosan-porous polylactic acid composite material to the polyvinyl alcohol solution and stirring to obtain an anti-mildew coating liquid B;
[0010] Step 5: Mix the anti-mildew coating liquid A and the anti-mildew coating liquid B in a ratio of 3:1 to 8:1 to obtain a mixed anti-mildew coating liquid, and apply the mixed anti-mildew coating liquid in a coating amount of 4-10g / m 2 The base paper of the photovoltaic glass mildew-proof paper is subjected to coating treatment to obtain a finished product.
[0011] The preparation method of the photovoltaic glass mildew-proof paper is as follows: the preparation of the nano-silver-coated carboxyethyl chitin is as follows: 0.05-0.2g of carboxyethyl chitin is added to 50-150ml of water by mass and ultrasonically dispersed for 20-40min, 10-30mg of silver nitrate is added, and the mixture is stirred at 100-200r / min for 20-40min. After the silver nitrate is completely and evenly dissolved, 5-15ml of 0.1% bovine serum albumin and 5-15ml of 0.5% sodium borohydride are added, and the pH value is adjusted to 8-9 with NaOH solution. Nitrogen is filled under oxygen-isolating conditions, and the mixture is reacted at 45-55°C for 3-5h. After the reaction is completed, the mixture is centrifuged at 5000-7000r / min, the supernatant is removed, and the mixture is washed with deionized water and centrifuged multiple times. After the reaction is completed, the mixture is vacuum-dried at 50-60°C to obtain the nano-silver-coated carboxyethyl chitin.
[0012] The preparation method of the above-mentioned photovoltaic glass mildew-proof paper is as follows: the preparation of the nano-silver-coated carboxyethyl chitin is as follows: 0.1g of carboxyethyl chitin is added to 100ml of water by mass and ultrasonically dispersed for 30 minutes, then 20mg of silver nitrate is added and stirred at 200r / min for 30 minutes. After the silver nitrate is completely and evenly dissolved, 10ml of 0.1% bovine serum albumin and 10ml of 0.5% sodium borohydride are added, and the pH value is adjusted to 8-9 with a 5% NaOH solution. Nitrogen is filled under oxygen-isolating conditions, and the reaction is carried out at 50°C for 4h. After the reaction, the reaction is carried out at a high speed of 6000r / min, and the supernatant is removed. The mixture is washed with deionized water and centrifuged three times. After the reaction is completed, the mixture is vacuum-dried at 55°C to obtain the nano-silver-coated carboxyethyl chitin.
[0013] The aforementioned method for preparing photovoltaic glass mildew-proof paper, wherein the modified montmorillonite is prepared by subjecting cationic carboxymethyl cellulose to an esterification reaction, adding the reaction product to montmorillonite, adding 30% ethanol, and ultrasonically treating the montmorillonite at room temperature for 1 hour, and then using a ball mill for high-speed grinding for 4 hours to finally obtain modified montmorillonite in which montmorillonite is loaded on the surface of cationic carboxymethyl cellulose.
[0014] The preparation method of the aforementioned photovoltaic glass mildew-proof paper is as follows: the preparation of the nano-silver-coated carboxyethyl chitin-modified montmorillonite composite material is as follows: 0.1-0.5g of nano-silver-coated carboxyethyl chitin is dissolved in deionized water, 10g-20g of modified montmorillonite is added, and a dilute sulfuric acid solution is added to adjust the pH value to 4, the total mass concentration of the nano-silver-coated carboxyethyl chitin and the modified montmorillonite is adjusted to 3-8wt% with 50% ethanol, the mixture is uniformly mixed, and the mixture is reacted at 55-65°C for 4-8h. After the reaction is completed, the pH value is adjusted to neutral with a NaOH solution, and the ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried, ground and pulverized, and then passed through a 100-mesh sample sieve, and then dry-heated at 120-140°C for 1.5-2.5h to obtain the nano-silver-coated carboxyethyl chitin-modified montmorillonite composite material.
[0015] The preparation method of the aforementioned photovoltaic glass mildew-proof paper is as follows: the preparation of the nano-silver-coated carboxyethyl chitin-modified montmorillonite composite material is as follows: 0.3 g of nano-silver-coated carboxyethyl chitin is dissolved in deionized water, 15 g of modified montmorillonite is added, and then a 0.1 mol / L dilute sulfuric acid solution is added to adjust the pH value to 4, the total mass concentration of the nano-silver-coated carboxyethyl chitin and the modified montmorillonite is adjusted to 5 wt% with 50% ethanol, the mixture is uniformly mixed, and the mixture is reacted at 60° C. for 6 h. After the reaction is completed, the pH value is adjusted to neutral with a 0.1 mol / L NaOH solution, and the ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried in a 105° C. oven, ground and pulverized, and passed through a 100-mesh sample sieve, and then dry-heated at 130° C. for 2 h to obtain the nano-silver-coated carboxyethyl chitin-modified montmorillonite composite material.
[0016] The preparation method of the aforementioned photovoltaic glass mildew-proof paper, the preparation of the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material is to ultrasonically treat 0.05-0.15g of nanosilver-coated carboxyethyl chitin and 10-15g of porous polylactic acid in 30-80ml of water for 0.5-2h, remove most of the water with a centrifuge, and then wash with deionized water multiple times, and then take the centrifuged solid and vacuum dry it at 50-60°C to obtain the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material.
[0017] The preparation method of the aforementioned photovoltaic glass mildew-proof paper, the preparation of the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material is to ultrasonically treat 0.1g of nanosilver-coated carboxyethyl chitin and 12g of porous polylactic acid in 50ml of water for 1h, remove most of the water with a centrifuge, and then wash with deionized water 3 times, and then take the centrifuged solid and vacuum dry it at 55°C to obtain the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material.
[0018] The preparation method of the above-mentioned photovoltaic glass mildew-proof paper, the preparation of the mildew-proof coating liquid A is to weigh a certain amount of polyvinyl alcohol, add it to water at 50-70°C, slowly stir it to completely dissolve it to make a 5% to 15% solution, and then add nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material, the addition amount is 3-8% of the amount of polyvinyl alcohol, and after fully stirring at 1600-2000r / min in a high-speed stirrer for 25-35 minutes, the mildew-proof coating liquid A is finally obtained.
[0019] The preparation method of the above-mentioned photovoltaic glass mildew-proof paper, the preparation of the mildew-proof coating liquid B is to weigh a certain amount of polyvinyl alcohol, add it to water at 55-65°C, slowly stir it to completely dissolve it to make a 5% to 15% solution, and then add nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material, the addition amount is 2-5% of the amount of polyvinyl alcohol, and after fully stirring at 1600-2000r / min in a high-speed stirrer for 25-35 minutes, the mildew-proof coating liquid B is finally obtained.
[0020] Compared to the prior art, the present invention utilizes nanosilver-coated carboxyethyl chitosan, modified montmorillonite, and porous polylactic acid to produce nanosilver-coated carboxyethyl chitosan-modified montmorillonite composite materials and nanosilver-coated carboxyethyl chitosan-porous polylactic acid composite materials. These two composite materials are then added to a polyvinyl alcohol solution to produce anti-mildew coating liquids A and B, respectively. Finally, these anti-mildew coating liquids A and B are used to impart anti-mildew properties to photovoltaic glass anti-mildew paper. This invention significantly improves the anti-mildew performance of photovoltaic glass anti-mildew paper. Furthermore, due to the sustained-release properties of the composite materials, the duration and effectiveness of the anti-mildew effect can be increased, thereby improving the performance of the photovoltaic glass anti-mildew paper under extreme conditions. Furthermore, the present invention provides new ideas for various other packaging materials requiring long-lasting anti-mildew properties, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the concentration standard curve of nanosilver coated carboxyethyl chitin;
[0022] Figure 2 This is the release curve of nanosilver-coated carboxyethyl chitosan in nanosilver-coated carboxyethyl chitosan-modified montmorillonite composite material. DETAILED DESCRIPTION
[0023] The present invention will be further described below with reference to the accompanying drawings and examples, but they are not intended to limit the present invention.
[0024] Example 1: A method for preparing photovoltaic glass mildew-proof paper, according to the following steps:
[0025] Step 1: Prepare nano-silver-coated carboxyethyl chitin using silver nitrate and carboxyethyl chitin; in this step, the preparation of the nano-silver-coated carboxyethyl chitin is as follows: 0.08g of carboxyethyl chitin is added to 80ml of water and ultrasonically dispersed for 25min, 15mg of silver nitrate is added, and the mixture is stirred at 180r / min for 30min. After the silver nitrate is completely and evenly dissolved, 15ml of 0.1% bovine serum albumin and 5ml of 0.5% sodium borohydride are added, and the pH value is adjusted to 8-9 with a 5% NaOH solution. The mixture is filled with nitrogen and oxygen-isolating conditions, reacted at 45°C for 5h, and centrifuged at 6500r / min after the reaction. After the supernatant is removed, the mixture is washed with deionized water and centrifuged three times. After the reaction, the mixture is vacuum-dried at 50-60°C to obtain the nano-silver-coated carboxyethyl chitin.
[0026] Step 2: Modifying montmorillonite to obtain modified montmorillonite, and preparing a nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material using nanosilver-coated carboxyethyl chitin and the modified montmorillonite. In this step, cationic carboxymethyl cellulose is subjected to an esterification reaction, and the reaction product is added to the montmorillonite. 30% ethanol is added, and the montmorillonite is ultrasonically treated at room temperature for 1 hour. The montmorillonite is then ball milled at high speed for 4 hours to obtain a modified montmorillonite in which the montmorillonite is supported on the surface of the cationic carboxymethyl cellulose.
[0027] In this step, the preparation of the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material is as follows: 0.4 g of nano-silver coated carboxyethyl chitin is dissolved in deionized water, 18 g of modified montmorillonite is added, and then a 0.1 mol / L dilute sulfuric acid solution is added to adjust the pH value to 4, the total mass concentration of the nano-silver coated carboxyethyl chitin and the modified montmorillonite is adjusted to 6 wt % with 50% ethanol, the mixture is uniformly mixed, and the mixture is reacted at 60° C. for 6 h. After the reaction is completed, the pH value is adjusted to neutral with a 0.1 mol / L NaOH solution, and the ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried and ground to pass through a 100-mesh sample sieve, and then dry-heated in an oven at 125° C. for 2.5 h to obtain the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material.
[0028] Step 3: Using nanosilver-coated carboxyethyl chitin and porous polylactic acid to prepare a nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material; in this step, the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material is prepared by ultrasonically treating 0.08 g of nanosilver-coated carboxyethyl chitin and 12 g of porous polylactic acid in 40 ml of water for 1.5 hours, removing most of the water with a centrifuge, and then washing with deionized water multiple times. Then, the centrifuged solid is vacuum-dried at 55° C. to obtain the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material.
[0029] Step 4: Add the nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material to the polyvinyl alcohol solution and stir to obtain an anti-mildew coating liquid A; add the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material to the polyvinyl alcohol solution and stir to obtain an anti-mildew coating liquid B; in this step, the anti-mildew coating liquid A is prepared by weighing a certain amount of polyvinyl alcohol, adding it to 65°C water, slowly stirring it to completely dissolve it to prepare a 10% solution, and then adding the nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material in an amount of 8% of the amount of polyvinyl alcohol, and stirring it thoroughly in a high-speed stirrer at 1800 r / min for 35 minutes to finally obtain the anti-mildew coating liquid A.
[0030] The mildew-proof coating liquid B is prepared by weighing a certain amount of polyvinyl alcohol, adding it to 60°C water, slowly stirring it to completely dissolve it to prepare a 10% solution, and then adding the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material in an amount of 2% of the amount of polyvinyl alcohol. After being fully stirred in a high-speed stirrer at 1800 r / min for 35 minutes, the mildew-proof coating liquid B is finally obtained.
[0031] Step 5: Mix the anti-mildew coating liquid A and the anti-mildew coating liquid B in a ratio of 4:1 to obtain a mixed anti-mildew coating liquid. Apply the mixed anti-mildew coating liquid at a coating amount of 5g / m 2 The base paper of the photovoltaic glass mildew-proof paper is subjected to coating treatment to obtain a finished product.
[0032] Example 2: A method for preparing photovoltaic glass mildew-proof paper, according to the following steps:
[0033] Step 1: Prepare nano-silver-coated carboxyethyl chitin using silver nitrate and carboxyethyl chitin; in this step, the preparation of the nano-silver-coated carboxyethyl chitin is as follows: 0.15g of carboxyethyl chitin is added to 120ml of water and ultrasonically dispersed for 40min, 25mg of silver nitrate is added, and the mixture is stirred at 130r / min for 40min. After the silver nitrate is completely and evenly dissolved, 8ml of 0.1% bovine serum albumin and 15ml of 0.5% sodium borohydride are added, and the pH value is adjusted to 8-9 with a 5% NaOH solution. The mixture is filled with nitrogen and oxygen-isolated, and reacted at 50°C for 4h. After the reaction, the mixture is centrifuged at 5500r / min, the supernatant is removed, and the mixture is washed with deionized water and centrifuged three times. After the reaction, the mixture is vacuum-dried at 60°C to obtain the nano-silver-coated carboxyethyl chitin.
[0034] Step 2: Modifying montmorillonite to obtain modified montmorillonite, and preparing a nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material using nanosilver-coated carboxyethyl chitin and the modified montmorillonite. In this step, cationic carboxymethyl cellulose is subjected to an esterification reaction, and the reaction product is added to the montmorillonite. 30% ethanol is added, and the montmorillonite is ultrasonically treated at room temperature for 1 hour. The montmorillonite is then ball milled at high speed for 4 hours to obtain a modified montmorillonite in which the montmorillonite is supported on the surface of the cationic carboxymethyl cellulose.
[0035] In this step, the preparation of the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material is as follows: 0.2 g of nano-silver coated carboxyethyl chitin is dissolved in deionized water, 15 g of modified montmorillonite is added, and then a 0.1 mol / L dilute sulfuric acid solution is added to adjust the pH value to 4, the total mass concentration of the nano-silver coated carboxyethyl chitin and the modified montmorillonite is adjusted to 4 wt% with 50% ethanol, the mixture is uniformly mixed, and the mixture is reacted at 55° C. for 5 h. After the reaction is completed, the pH value is adjusted to neutral with a 0.1 mol / L NaOH solution, and the ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried and ground to pass through a 100-mesh sample sieve, and then dry-heated in an oven at 130° C. for 1.5 h to obtain the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material.
[0036] Step 3: Using nanosilver-coated carboxyethyl chitin and porous polylactic acid to prepare a nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material; in this step, the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material is prepared by ultrasonically treating 0.15 g of nanosilver-coated carboxyethyl chitin and 15 g of porous polylactic acid in 70 ml of water for 1.5 hours, removing most of the water with a centrifuge, and then washing with deionized water multiple times. Then, the centrifuged solid is vacuum-dried at 60° C. to obtain the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material.
[0037] Step 4: Add the nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material to the polyvinyl alcohol solution and stir to obtain an anti-mildew coating liquid A; add the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material to the polyvinyl alcohol solution and stir to obtain an anti-mildew coating liquid B; in this step, the anti-mildew coating liquid A is prepared by weighing a certain amount of polyvinyl alcohol, adding it to 55°C water, slowly stirring it to completely dissolve it to prepare a 15% solution, and then adding the nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material in an amount of 4% of the amount of polyvinyl alcohol, and stirring it thoroughly with a high-speed stirrer at 2000 r / min for 25 minutes to finally obtain the anti-mildew coating liquid A.
[0038] The mildew-proof coating liquid B is prepared by weighing a certain amount of polyvinyl alcohol, adding it to 65°C water, slowly stirring it to completely dissolve it to prepare a 15% solution, and then adding a nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material in an amount of 4% of the amount of polyvinyl alcohol. After being fully stirred in a high-speed stirrer at 1600 r / min for 25 minutes, the mildew-proof coating liquid B is finally obtained.
[0039] Step 5: Mix the anti-mildew coating liquid A and the anti-mildew coating liquid B in a ratio of 6:1 to obtain a mixed anti-mildew coating liquid. Apply the mixed anti-mildew coating liquid at a coating amount of 5g / m 2 The base paper of the photovoltaic glass mildew-proof paper is subjected to coating treatment to obtain a finished product.
[0040] Example 3: A method for preparing photovoltaic glass mildew-proof paper, according to the following steps:
[0041] Step 1: Prepare nano-silver-coated carboxyethyl chitin using silver nitrate and carboxyethyl chitin; in this step, the preparation of the nano-silver-coated carboxyethyl chitin is as follows: 0.1g carboxyethyl chitin is added to 100ml water by mass and ultrasonically dispersed for 30min, 20mg of silver nitrate is added, and the mixture is stirred at 200r / min for 30min. After the silver nitrate is completely and evenly dissolved, 10ml of 0.1% bovine serum albumin and 10ml of 0.5% sodium borohydride are added, and the pH value is adjusted to 8-9 with a 5% NaOH solution. The mixture is filled with nitrogen and oxygen-isolating conditions, reacted at 50°C for 4h, and centrifuged at 6000r / min after the reaction is completed. After the supernatant is removed, the mixture is washed with deionized water and centrifuged three times. After the reaction is completed, the mixture is vacuum-dried at 55°C to obtain the nano-silver-coated carboxyethyl chitin.
[0042] Step 2: Modifying montmorillonite to obtain modified montmorillonite, and preparing a nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material using nanosilver-coated carboxyethyl chitin and the modified montmorillonite. In this step, cationic carboxymethyl cellulose is subjected to an esterification reaction, and the reaction product is added to the montmorillonite. 30% ethanol is added, and the montmorillonite is ultrasonically treated at room temperature for 1 hour. The montmorillonite is then ball milled at high speed for 4 hours to obtain a modified montmorillonite in which the montmorillonite is supported on the surface of the cationic carboxymethyl cellulose.
[0043] In this step, the preparation of the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material is as follows: 0.3 g of nano-silver coated carboxyethyl chitin is dissolved in deionized water, 15 g of modified montmorillonite is added, and then a 0.1 mol / L dilute sulfuric acid solution is added to adjust the pH value to 4, the total mass concentration of the nano-silver coated carboxyethyl chitin and the modified montmorillonite is adjusted to 5 wt% with 50% ethanol, the mixture is uniformly mixed, and the mixture is reacted at 60° C. for 6 h. After the reaction is completed, the pH value is adjusted to neutral with a 0.1 mol / L NaOH solution, and the ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried, ground and pulverized, and then passed through a 100-mesh sample sieve. It is then dry-heated in an oven at 130° C. for 2 h to obtain the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material.
[0044] Step 3: Using nanosilver-coated carboxyethyl chitin and porous polylactic acid to prepare a nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material; in this step, the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material is prepared by ultrasonically treating 0.1 g of nanosilver-coated carboxyethyl chitin and 12 g of porous polylactic acid in 50 ml of water for 1 hour, removing most of the water with a centrifuge, and then washing with deionized water three times. Then, the centrifuged solid is vacuum-dried at 55° C. to obtain the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material.
[0045] Step 4: Add the nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material to the polyvinyl alcohol solution and stir to obtain an anti-mildew coating liquid A; add the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material to the polyvinyl alcohol solution and stir to obtain an anti-mildew coating liquid B; in this step, the anti-mildew coating liquid A is prepared by weighing a certain amount of polyvinyl alcohol, adding it to 60°C water, slowly stirring it to completely dissolve it to prepare a 10% solution, and then adding the nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material in an amount of 5% of the amount of polyvinyl alcohol, and stirring it thoroughly in a high-speed stirrer at 1800 r / min for 30 minutes to finally obtain the anti-mildew coating liquid A.
[0046] The mildew-proof coating liquid B is prepared by weighing a certain amount of polyvinyl alcohol, adding it to 60°C water, slowly stirring it to completely dissolve it to prepare a 10% solution, and then adding a nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material in an amount of 3% of the amount of polyvinyl alcohol. After being fully stirred in a high-speed stirrer at 1800 r / min for 30 minutes, the mildew-proof coating liquid B is finally obtained.
[0047] Step 5: Mix the anti-mildew coating liquid A and the anti-mildew coating liquid B in a ratio of 5:1 to obtain a mixed anti-mildew coating liquid. Apply the mixed anti-mildew coating liquid at a coating amount of 6 g / m 2The base paper of the photovoltaic glass mildew-proof paper is subjected to coating treatment to obtain a finished product.
[0048] Example 4: This example is to test the intermediate product obtained in the steps of Example 3 and the photovoltaic glass mildew-proof paper sample obtained at the end. At the same time, in step 5, the coating amount of the mildew-proof coating liquid is 8g / m2 in addition to the 8g / m2 in Example 3. 2 In addition, it also includes 0g / m 2 , 2g / m 2 , 4g / m 2 , 6g / m 2 and 10g / m 2 The specific experimental tests are as follows:
[0049] 1. Contact angle measurement
[0050] The contact angle test is used to test the hydrophobicity of the coated sample. The coating was carried out using a coating machine with a coating amount of 0, 2, 4, 6, 8 and 10 g / m 2 Then, the static drop method was used to test the initial contact angle of each sample. The test liquid was polar liquid deionized water, and the liquid volume was 6μL. The initial contact angle was calculated using image analysis. Five replicates were tested under each condition and the average value was calculated. Table 1 shows the changes in the contact angle of paper samples under different coating amounts:
[0051] Coating amount Contact angle° 0 45 2 65.3 4 87.4 6 93.7 8 104.2 10 97.6
[0052] Table 1
[0053] From the test results, the contact angle of the paper increased significantly after coating, and the coating amount was 8g / m 2 When the amount of coating liquid is increased, the contact angle reaches 104.2, which shows that the coating liquid has a good performance finishing effect on the paper surface, can significantly improve the water resistance of the paper, reduce the exposure of the hydrophilic groups of the paper, and with the increase of the dosage, the waterproof performance is enhanced, and the mildew resistance of the paper is improved.
[0054] 2. Accelerated release test;
[0055] Carboxyethyl chitin was used as a content gradient KBr infrared test piece, and the standard curve equation of carboxyethyl chitin concentration and characteristic peak absorbance was obtained by testing and calculating. Figure 1 The concentration standard curve of carboxyethyl chitosan is such that the fitting accuracy of the standard curve can meet the requirements of this experiment. Its equation is:
[0056] Y=5.08x-0.1,R 2 =0.9999;
[0057] The nanosilver-coated carboxyethyl chitin-modified montmorillonite and the nanosilver-coated carboxyethyl chitin porous polylactic acid composite mildew-proof composite containing an equal amount of 50 mg of carboxyethyl chitin were placed in a 3500Da dialysis bag. The two ports were sealed with a dialysis bag clamp and placed in 500 mL of deionized water respectively and slowly magnetically stirred. The dialysis bag was taken out every hour, and the deionized water was rotary evaporated to about 5 ml and then freeze-dried. The dried powder was used for infrared testing and analyzed at 2925 cm -1 The absorbance of the characteristic absorption peak of -CH2 is measured, and then its content is calculated according to the standard curve, as shown in the following figure: Figure 2 The release curve of nanosilver-coated carboxyethyl chitosan within 48 hours after loading with nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite mildew-proof composite material is shown. It can be seen that nanosilver-coated carboxyethyl chitosan is released in stages: the first stage is the rapid release stage (0-8h). This is because after contacting water, polypropylene alcohol swells, and more nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite mildew-proof materials are exposed. As the degree of swelling increases, more is exposed. Therefore, a large amount of nanosilver-coated carboxyethyl chitosan will be released in the early stage. As time goes by, the content of nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite mildew-proof materials in water stabilizes, and the stable release stage is reached at this time (after 12h). At this stage, the unstable hydrogen bonds formed by the nanosilver-coated carboxyethyl chitosan on the modified montmorillonite sheets and the nanosilver-coated carboxyethyl chitosan in the inner pores of the porous polylactic acid are broken. However, since the hydrogen bonds are mainly inside, the nanosilver-coated carboxyethyl chitosan is difficult to dissolve, so the release rate is slow and stable.
[0058] 3. Antibacterial test;
[0059] The coated paper was cut into 6mm diameter discs using a hole punch. After high-temperature sterilization, these discs were placed radially at 5cm intervals. Because the antibacterial material on the coated paper surface is slowly released, it inhibits bacterial growth, forming inhibition zones larger than 7mm in diameter. The diameters of the inhibition zones were measured after one week in a potato dextrose agar (PDA) incubator at 28°C and 85% humidity. Table 2 shows the antibacterial properties of different coating amounts.
[0060]
[0061]
[0062] Table 2
[0063] Judging from the test results, the samples without nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite anti-mildew materials have no antibacterial effect. The material has antibacterial effect on both mold and color-changing bacteria. With the increase of the use of nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite anti-mildew composite materials, the antibacterial effect is improved. The order of antibacterial effect is: Penicillium citrinum > Trichoderma viride > Aspergillus niger > Diplodia theobromin. This is mainly because nanosilver-coated carboxyethyl chitosan can destroy the colloidal state of the contents in the cytoplasm, causing them to flocculate and denature, making them unable to carry out normal physiological activities, or directly interfere with the negatively charged genetic material DNA and RNA in the cells, thereby inhibiting the reproduction of organisms and achieving antibacterial effects.
[0064] 4. Dispersion performance and stability of coating liquid;
[0065] Nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite mildew-proof composites were prepared according to the coating liquid formulation. Their viscosity change over 24 hours at room temperature and their static delamination time were measured using a viscometer. Table 3 shows the viscosity change and delamination time of the coating liquid after standing.
[0066]
[0067] Table 3
[0068] It can be seen from Table 3 that the viscosity of the coating liquid prepared with nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite anti-mildew materials is low, and the initial viscosity does not change much over time. The modified montmorillonite has the effect of enhancing the viscosity of the coating liquid, but its viscosity decreases after being compounded with the hydrophilic nanosilver-coated carboxyethyl chitosan. Therefore, the viscosity of the coating liquid is not high and the stability is good. After standing for 8 days, the water in the coating liquid partially evaporates, and a small amount of condensed water can be seen on the mouth of the cup covered with plastic wrap. After standing for 14 days, slight stratification will occur, indicating that polyvinyl alcohol has a good stabilizing effect on the dispersion of nanosilver-coated carboxyethyl chitosan-modified montmorillonite and nanosilver-coated carboxyethyl chitosan porous polylactic acid composite anti-mildew materials, and the entire dispersion system is relatively stable.
[0069] In summary, the present invention uses nanosilver-coated carboxyethyl chitosan to prepare nanosilver-coated carboxyethyl chitosan-modified montmorillonite composite materials and nanosilver-coated carboxyethyl chitosan-porous polylactic acid composite materials, respectively. The two composite materials are then added to a polyvinyl alcohol solution to obtain mildew-proof coating liquid A and mildew-proof coating liquid B, respectively. Finally, mildew-proof coating liquid A and mildew-proof coating liquid B are used to impart mildew-proof properties to photovoltaic glass mildew-proof paper. As a result, the present invention can greatly improve the mildew-proof performance of photovoltaic glass mildew-proof paper. Moreover, because the composite material has the advantage of slow release, it can increase the duration and effectiveness of mildew-proofing, thereby improving the performance of photovoltaic glass mildew-proof paper under extreme conditions. Furthermore, the present invention provides new ideas for various other packaging materials that require long-term mildew-proofing properties and has broad application prospects.
Claims
1. A method for preparing photovoltaic glass mildew-proof paper, characterized by: The steps include: Step 1: preparing nano-silver coated carboxyethyl chitin by using silver nitrate and carboxyethyl chitin; Step 2: preparing a nano-silver coated carboxyethyl chitin-modified montmorillonite composite material by using nano-silver coated carboxyethyl chitin and modified montmorillonite; Step 3, using nano-silver coated carboxyethyl chitin and porous polylactic acid to prepare a nano-silver coated carboxyethyl chitin-porous polylactic acid composite material; Step 4: adding the nano-silver coated carboxyethyl chitosan-modified montmorillonite composite material to the polyvinyl alcohol solution and stirring to obtain an anti-mildew coating liquid A; adding the nano-silver coated carboxyethyl chitosan-porous polylactic acid composite material to the polyvinyl alcohol solution and stirring to obtain an anti-mildew coating liquid B; Step 5: Mix the anti-mildew coating liquid A and the anti-mildew coating liquid B in a ratio of 3:1 to 8:1 to obtain a mixed anti-mildew coating liquid. Apply the mixed anti-mildew coating liquid in a coating amount of 4-10 g / m 2 The base paper of the photovoltaic glass mildew-proof paper is coated to obtain a finished product; The preparation of the nano-silver-coated carboxyethyl chitin comprises the following steps: adding 0.05-0.2 g of carboxyethyl chitin to 50-150 ml of water by mass and dispersing the mixture by ultrasonication for 20-40 minutes; then adding 10-30 mg of silver nitrate and stirring the mixture at 100-200 r / min for 20-40 minutes; after the silver nitrate is completely and evenly dissolved, adding 5-15 ml of 0.1% bovine serum albumin and 5-15 ml of 0.5% sodium borohydride by mass; adjusting the pH value to 8-9 with a NaOH solution; and reacting the mixture at 45-55° C. for 3-5 hours under nitrogen-insulated conditions. After the reaction is completed, the mixture is centrifuged at 5000-7000 r / min, the supernatant is removed, and the mixture is washed with deionized water and centrifuged multiple times. Finally, the mixture is vacuum-dried at 50-60° C. to obtain the nano-silver-coated carboxyethyl chitin. The modified montmorillonite is prepared by subjecting cationic carboxymethyl cellulose to an esterification reaction, adding the reaction product to montmorillonite, adding 30% ethanol, and subjecting the montmorillonite to ultrasonic treatment at room temperature for 1 hour, and then using a ball mill for high-speed grinding for 4 hours to finally obtain the modified montmorillonite in which the montmorillonite is supported on the surface of the cationic carboxymethyl cellulose; The preparation method of the nano-silver coated carboxyethyl chitin-porous polylactic acid composite material comprises the following steps: ultrasonically treating 0.05-0.15 g of nano-silver coated carboxyethyl chitin and 10-15 g of porous polylactic acid in 30-80 ml of water for 0.5-2 h, removing most of the water with a centrifuge, washing the mixture with deionized water for multiple times, and then vacuum drying the centrifuged solid at 50-60° C. to obtain the nano-silver coated carboxyethyl chitin-porous polylactic acid composite material.
2. The method for preparing the photovoltaic glass mildew-proof paper according to claim 1, characterized in that: The preparation of the nano-silver-coated carboxyethyl chitin comprises the following steps: taking 0.1 g of carboxyethyl chitin by mass, adding it to 100 ml of water, and dispersing it by ultrasonication for 30 minutes; then adding 20 mg of silver nitrate, stirring at 200 r / min for 30 minutes; after the silver nitrate is completely and evenly dissolved, adding 10 ml of 0.1% bovine serum albumin and 10 ml of 0.5% sodium borohydride by mass; adjusting the pH value to 8-9 with a 5% NaOH solution by mass; filling the solution with nitrogen under oxygen-isolating conditions, reacting at 50° C. for 4 hours; and after the reaction, centrifuging at 6000 r / min at high speed, removing the supernatant, washing with deionized water, and centrifuging three times. Finally, vacuum drying is performed at 55° C. to obtain the nano-silver-coated carboxyethyl chitin.
3. The method for preparing the photovoltaic glass mildew-proof paper according to claim 1, characterized in that: The nano-silver coated carboxyethyl chitin-modified montmorillonite composite material is prepared by dissolving 0.1-0.5 g of nano-silver coated carboxyethyl chitin in deionized water, adding 10-20 g of modified montmorillonite, and then adding a dilute sulfuric acid solution to adjust the pH value to 4. The total mass concentration of the nano-silver coated carboxyethyl chitin and the modified montmorillonite is adjusted to 3-8 wt % with 50% ethanol. After the mixture is evenly mixed, the mixture is reacted at 55-65° C. for 4-8 hours. After the reaction is completed, the pH value is adjusted to neutral with a NaOH solution. The ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried, ground, and pulverized to pass through a 100-mesh sample sieve. The mixture is then dry-heated at 120-140° C. for 1.5-2.5 hours to obtain the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material.
4. The method for preparing the photovoltaic glass mildew-proof paper according to claim 3, characterized in that: The nano-silver coated carboxyethyl chitin-modified montmorillonite composite material is prepared by dissolving 0.3 g of nano-silver coated carboxyethyl chitin in deionized water, adding 15 g of modified montmorillonite, and then adding 0.1 mol / L dilute sulfuric acid solution to adjust the pH value to 4. The total mass concentration of the nano-silver coated carboxyethyl chitin and the modified montmorillonite is adjusted to 5 wt% with 50% ethanol. After the mixture is evenly mixed, the mixture is reacted at 60° C. for 6 h. After the reaction is completed, the pH value is adjusted to neutral with 0.1 mol / L NaOH solution. The ethanol is recovered by rotary evaporation for use in the next reaction. The remaining solid is dried in an oven at 105° C., ground and pulverized, and passed through a 100-mesh sample sieve. The mixture is then dry-heated at 130° C. for 2 h to obtain the nano-silver coated carboxyethyl chitin-modified montmorillonite composite material.
5. The method for preparing the photovoltaic glass mildew-proof paper according to claim 1, characterized in that: The nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material is prepared by ultrasonically treating 0.1 g of nanosilver-coated carboxyethyl chitin and 12 g of porous polylactic acid in 50 ml of water for 1 hour, removing most of the water with a centrifuge, and then washing with deionized water three times. The centrifuged solid is then vacuum-dried at 55° C. to obtain the nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material.
6. The method for preparing the photovoltaic glass mildew-proof paper according to claim 1, characterized in that: The mildew-proof coating liquid A is prepared by weighing a certain amount of polyvinyl alcohol, adding it to water at 50-70° C., slowly stirring it to completely dissolve it to form a 5% to 15% solution, then adding a nanosilver-coated carboxyethyl chitin-modified montmorillonite composite material in an amount of 3-8% of the amount of polyvinyl alcohol, and fully stirring it in a high-speed stirrer at 1600-2000 r / min for 25-35 minutes to finally obtain the mildew-proof coating liquid A.
7. The method for preparing the photovoltaic glass mildew-proof paper according to claim 1, characterized in that: The mildew-proof coating liquid B is prepared by weighing a certain amount of polyvinyl alcohol, adding it to water at 55-65° C., slowly stirring it to completely dissolve it to prepare a 5% to 15% solution, and then adding a nanosilver-coated carboxyethyl chitin-porous polylactic acid composite material in an amount of 2-5% of the amount of polyvinyl alcohol. After being fully stirred in a high-speed stirrer at 1600-2000 r / min for 25-35 minutes, the mildew-proof coating liquid B is finally obtained.
Citation Information
Patent Citations
Liquid-phase synthesis method of silver-chitosan and / or chitosan derivative nanocomposite
CN102327284A
Antibiosis composite materials, preparing method of antibiosis composite materials and antibiosis liquid
CN103131108A
Method for producing long-lasting antiseptic glass interval paper
CN106702806A